(3GdJHUQI aj GdfMhs - (3CHh eMeO YHO Gddg Hf Ydj Hf ESMGb GdUjeQj, GHf edchf GdCTHjdj,J (B584 (3g` s
(3ChdgG (B:s
(3bGd YHO Gddg Hf Ydi Hf ESMGb GdUejQi (B: (3gPG cJGH LeYJ ajg ef CUhd Yde GdfMh haQhYg eG ChVMJ HjGfg hHjfJ HQgGfg s
(3BNQgG (B:s
(3jfJgi HGdcdGe Ydi GdEOZGe , hGdSWhQ GdCNjQI eJCcdI heG jecf bQGAJg bhdg aUd hGdgGA JOZe ai eKdgG s
(3HChdg GdfSNI JMHjS ef GdSdWGJ CMeO GdefUhQ Ydi NRGfI GdbQhjjf hJGQjN GdJMHj ZjQ hGVMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3NRGfI LGeYI GdbQhjjf HaGS (B(517 / 40) s
Keywords: (3GdfMhs